Genome-wide detection of selective signatures in a Jinhua pig population - Zhong XU; Hao SUN; Zhe ZHANG; Qing-bo ZHAO; Babatunde Shittu OLASEGE; Li Qiu-meng; Yang YUE; Pei-pei MA; Xiang-zhe ZHANG; Qi-shan WANG; Yu-chun PAN (Journal of Integrative Agriculture, 2020)
The aim of this study was to detect evidence for signatures of recent selection in the Jinhua pig genome. These results can be useful to better understand the regions under selection in Jinhua pigs and might shed some lights on groups of genes that control production traits. In the present study, we performed extended haplotype homozygosity (EHH) tests to identify significant core regions in 202 Jinhua pigs. A total of 26 161 core regions spanning 636.42 Mb were identified, which occupied approximately 28% of the genome across all autosomes, and 1 158 significant (P<0.01) core haplotypes were selected. Genes in these regions were related to several economically important traits, including meat quality, reproduction, immune responses and exterior traits. A panel of genes including ssc-mir-365-2, KDM8, RABEP2, GSG1L, RHEB, RPH3AL and a signal pathway of PI3K-Akt were detected with the most extreme P-values. The findings in our study could draw a comparatively genome-wide map of selection signature in the pig genome, and also help to detect functional candidate genes under positive selection for further genetic and breeding research in Jinhua and other pigs.